1994
DOI: 10.1021/j100060a038
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Nonionic Micelles and a Nonionic Polymer Studied by Fourier Transform NMR Self-Diffusion

Abstract: The interaction between octaethylene glycol mono-n-dodecyl ether (C12Eg) and ethylhydroxyethyl cellulose (EHEC) in aqueous solution has been studied by measuring the C&g self-diffusion coefficient in the presence of EHEC at 25 OC. Micelle diffusion is influenced by the polymer in two ways, i.e. obstruction due to the polymer network and association of micelles to the polymer chains. It is demonstrated that, from studies using polymers of different polarity, a separation between obstruction and association effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…C 12 EO 8 has a cmc of 9 × 10 -5 mol kg -1 at 25 °C in water so in 4 mmol kg -1 solution it will predominantly be in the form of micelles. Zhang et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C 12 EO 8 has a cmc of 9 × 10 -5 mol kg -1 at 25 °C in water so in 4 mmol kg -1 solution it will predominantly be in the form of micelles. Zhang et al …”
Section: Resultsmentioning
confidence: 99%
“…C 12 EO 8 has a cmc of 9 × 10 -5 mol kg -1 at 25 °C in water so in 4 mmol kg -1 solution it will predominantly be in the form of micelles. Zhang et al 21 concluded from results of NMR self-diffusion measurements on the EHEC A-C 12 EO 8 system that there is an attractive interaction between C 12 EO 8 micelles and the polymer.…”
Section: Phasementioning
confidence: 99%
“…This indicates that the polymer interacts preferably with micelles of OTG. The nonionic surfactant C 12 E 8 interacts in the form of micelles with ethylhydroxyethyl cellulose in aqueous solution 49 and other nonionic surfactants can be expected to interact in the same way as pseudo-polymers. We believe that if the polymer influences the aggregation of a surfactant that will lead to a lowering of the aggregation concentration c.a.c.…”
Section: Surfactants and Homopolymersmentioning
confidence: 99%
“…The micelle sizes are similar to and without polymer present, whereas aggregation numbers are similar or slightly lower than those of micelles forming in the absence of polymer. When a surfactant is added to an aqueous solution of polymer having hydrophobic segments, then due to a hydrophobic effect, it would become thermodynamically favorable for the surfactant to adsorb to polymer or even to form aggregates with a hydrophobic portion of the polymer. …”
Section: Introductionmentioning
confidence: 99%